Effect of crossbreeding on growth characteristics in zebu cattle of Chorotega region - Madrigal-Valverde, Mónica; Camacho-Sandoval, Jorge; Salas-Durán, Catalina (Agronomía Mesoamericana, 2019)
Introduction. There is little research about the effect of crossbred between Bos indicus * Bos indicus breeding, however, crossbreeding is an important optimization’s tool used by the livestock producers. Objective. The objective of this study was to determine the behavior of growth characteristics on different proportions of Bos indicus breed crosses. Materials and methods. The analysis was made based on production records of a selected cattle farm with Brahman, Nelore and commercial stock located in the North Pacific region, Costa Rica. The records of 4.294 animals, collected during the 2002-2012 period in the farm, were used; the breed groups included in the study were: Brahman, Nelore, Guzerat, ½ Brahman ½ Nelore, ½ Brahman ½ Guzerat, ¼ Brahman ¾ Nelore, and ¼ Nelore ¾ Brahman. Birth weight, weaning weight, weaning daily weight gain, year old weight, year old daily weight gain, 18 months weight, and 18 months daily weight gain were analyzed according to the breed group of the offspring and the parents. In addition, the non-additive effects (sex, season of birth and year of birth) and their influence on the characteristics were analyzed. Results. It was found that the Brahman, Nelore and ¼ Nelore ¾ Brahman breed groups had the highest weights at all ages, male animals presented higher weights for most of the analyzed characteristics (P <0.05); the animals born in the rainy season presented the highest weights for all the characteristics, in relation to the dry season, while the year of birth did not present trends. The study concluded that the breed group of the mother influenced the early ages of the offspring and the breed group of the father caused differences after one year of age. Likewise, the study concluded that the variables sex and season of birth presented defined behaviors, while the year of birth have fluctuating results. Conclusion. In crossbreds Bos indicus, the breed group of the progenitors have influences in the growth characteristics of progeny.